Importance of Green Supply Chain Management in Algerian Construction Industry towards sustainable development - Harouache, Ahmed; Chen, Goh Kai; Sarpin, Norliana Binti; Hamawandy, Nawzad Majeed; Jaf, Rizgar Abdullah Sabir; Qader, Khowanas Saeed; Jalal, Farman Badran; Azzat, Rezan Salahaddin (The journal of contemporary issues in business and government, 2021)
The construction industry is an important business sector providing physical equipment and infrastructure through supply and demand patterns that have a strong indirect impact on other industries. Construction projects require materials and products from other industries such as production and buildings and infrastructure for the benefit of those industries. In terms of economic growth, the building industry is economically important and has strong ties with other segments of the economy especially an important sector of economic growth and expansion in developing countries. The capital market is one of the most important parts of the economy, that it is not covered they’re important to anyone (MIR et al., 2020). Sustainable development issues are more than ever focused today on how communities view growth and the responsibility of the government to create ways to adapt to growth and to reduce the carbon footprint of human settlements. This paper has established a methodological basis for potential analysis in the construction industry with a view to the scale of application of green supply chain management in Algerian construction industry. The significance and scope of the study are explained in the paper.